022 Updated safety of cladribine tablets in multiple sclerosis patients: integrated safety analysis and post-approval data. Issue 6 (27th May 2022) - Cook, Stuart; Giovannoni, Gavin; Leist, Thomas; Comi, Giancarlo; Syed, Sana; Nolting, Axel; Damian, Doris; Schick, Regina; Jack, Dominic
Abstract : Background: This analysis updates on the previously reported serious treatment emergent adverse event (TEAE) profile of cladribine tablets (CT) 10mg (cumulative dose 3.5mg/kg [CT3.5] over 2 years) following integration of final data from the PREMIERE registry and post-approval safety data from worldwide sources. Methods: The monotherapy oral cohort (CT3.5, N=923, patient-years [PY]=3936.69; placebo, N=641, PY=2421.47) was derived from the CLARITY, CLARITY Extension and ORACLE-MS trials plus the PREMIERE registry. Adjusted adverse event incidences-per-100PY (Adj-AE-per-100PY) were calculated, cumulative to end of PREMIERE (October 2018). Results: Patient characteristics were balanced between groups. Adj-AE-per-100PY for ≥1 serious TEAE were: 3.80 (CT3.5), 3.05 (placebo); for serious lymphopenia (preferred term [PT]): 0.10 (CT3.5), 0 (placebo); for serious infections and infestations (system organ class): 0.60 (CT3.5), 0.42 (placebo); for serious herpes zoster (PT): 0.05 (CT3.5), 0 (placebo); and malignant tumours: 0.26 (CT3.5), 0.12 (placebo). Post-approval sources reported 1622 AEs in the Periodic Benefit-Risk Evaluation Report (275 were serious); none repre- sented a new safety signal. Conclusions: No new major safety findings for cladribine tablets were identified in this finalised integrated dataset containing final data from the PREMIERE registry. Findings are consistent with previously published integrated safety analyses. No new safety signals were identified from post-approval safety data. CLARITY: NCT00213135 . CLARITY Extension: NCT00641537 . ORACLE-MS: NCT00725985 . PREMIERE: NCT01013350 g.giovannoni@qmul.ac.uk